Key stakeholder perspectives on challenges and opportunities for rural HPV vaccination in North and South Carolina - Laura J. Fish; Sayward E Harrison; Jodi-Ann McDonald; Valerie Yelverton; Charnetta Williams; Emmanuel B. Walter; Lavanya Vasudevan (Taylor & Francis Group, 2022)
The objective of this study was to identify factors at the individual, provider, and systems levels that serve as challenges or opportunities for increasing adolescent vaccination-including Human Papillomavirus (HPV) vaccination-in rural communities in the southern United States (US). As part of a broader study to increase HPV vaccine uptake in the southern US, we conducted in-depth interviews with vaccination stakeholders representing public health and education agencies in North Carolina (NC) and South Carolina (SC). Fourteen key stakeholders were recruited using purposive sampling to obtain insights into challenges and solutions to rural-urban disparities in HPV vaccination coverage. Stakeholders were also queried about their experiences and attitudes toward school-based vaccination promotion programs and campaigns. We used a rapid qualitative approach to analyze the data. Stakeholders identified factors at the individual, provider, and systems levels that serve as challenges to vaccination in rural communities. Similar to previous studies, stakeholders mentioned challenges with healthcare access and vaccine-related misconceptions that pose barriers to HPV vaccination for rural residents. Systems-level challenges identified included limited access to high-speed internet in rural areas that may impact providers' ability to interface with state-level digital systems such as the vaccination registry. Stakeholders identified a number of opportunities to increase HPV vaccination coverage, including through school-based health promotion programs. Stakeholders strongly supported school-based programs and approaches to strengthen confidence and demand for HPV vaccination and to help address persistent social determinants and system level factors that pose challenges to HPV vaccination coverage in many rural areas.